Lithophagia in a Child: Unraveling the Puzzle of Celiac Disease - Koundinya Kalvala; Snehavardhan Pandey; Smita Vilasrao Kokitkar; Ashish Bavdekar (Indian Pediatrics Case Reports)
Background: Celiac disease (CD) is known to present with a wide spectrum of gastrointestinal and non-gastrointestinal manifestations. Although pica may be associated with low iron stores in CD, lithophagia as an extreme form of pica, is rarely reported in CD. Clinical Description: A 9-year-old boy presented with abdominal pain, without any vomiting, constipation, or diarrhea. On examination, he was overweight with mild pallor, and diffuse abdominal tenderness, without any palpable lump. Management and Outcome: Investigations revealed hemoglobin of 10.7 g/dL, with microcytic hypochromic red blood cells and very low ferritin levels. The abdominal radiograph showed radio-opaque foreign bodies in the entire large bowel and rectum. A review of history revealed lithophagia. These findings in a child with adequate nutrition, with no psychological disorder, raised suspicion of CD. Raised tissue transglutaminase antibody along with villous atrophy on duodenal biopsy confirmed the diagnosis of CD. The patient was treated with lactulose enemas, followed by iron supplementation and a gluten-free diet. Lithophagia resolved with these measures. Conclusion: The case highlights that lithophagia may be the only symptom in a child with CD. A high index of suspicion for CD needs to be kept in an otherwise psychologically normal, nutritionally adequate child having lithophagia.